The Dream of Freedom and Fear of It (Tyranny and Vassalage in ’The Master Is Coming Tomorrow’ by Petar Sarić) - Jeftimijević Mihajlović, Marija S. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The history of Serbian literature originating in Kosovo and Metohija during the second half of the previous century values Peter Sarić the most by his novel The Master is Coming Tomorrow, although he penned seven novels. The Master Is Coming Tomorrow is the image of power which, instead of protecting human rights, is transformed into the instrument of violence. It is the image of tyrant and tyranny, and it is at the same time a caricature of people – vassals, who out of fear, rather humbly languish in the so-called freedom, zealously shouting the Master’s name. One gets the impression that the writer wanted to portray vassalage in a satirical way more than tyranny. This thoroughly psychological characteristic of vassals, and power-holders of strong autocracy, makes Sarić a modern story-teller who has the courage and literary talent to dive into the deepest secrets of human nature, exposing the darkest corners of human psyche, something people are not willing to speak about. It is the novelty in the literature created in this area during the second half of the previous century; no other literary creation so clearly and precisely profiles the collective consciousness of one nation or the individuality of a ruler. In this novel, Sarić reveals a new face of patriarchal culture and the patriarchal system of the Montenegrin community. At the same time, Sarić confirms a known face of history, since each absolute power is based on identical levers of unscrupulous tyrants and humiliated, obedient people who resigned themselves to such a system.